Jaw function after oral appliance treatment of obstructive sleep apnea. - Dr Eva Nohlert; Prof Åke Tegelberg; Prof Thomas List; Assoc prof Göran Isacsson (Elsevier, 2023)
Aim or Purpose: To assess changes in symptoms and clinical findings related to jaw function after 1 year of treating Obstructive Sleep Apnea (OSA) with an Oral Appliance (OA). Material and Methods: 302 patients (males 76%) with OSA were randomized to bibloc (n=146) or monobloc (n=156) appliance treatment (with previously reported equal efficacy). At baseline and at 1-y-follow-up a questionnaire related to symptoms and signs was used, including i.a. Jaw Functional Limitation Scale (JFLS-8). Furthermore, a clinical examination of jaw function and mobility, dental occlusion and tenderness in temporomandibular joints (TMJs) and masticatory muscles was performed. Results: 192 patients completed the 1-y follow-up (males 73%, mean age 55; sd 11).No change was seen at the follow-up in JFLS score or in clinical measurements of jaw mobility, dental occlusion or pain/tenderness upon palpation of TMJs and masticatory muscles.The patients described no change in symptoms at the follow-up, except for reduced morning headache (p<.001) and increased frequency of difficulties in opening the mouth or chewing upon awakening (p=.002) as well as subjectively noticed changes in dental occlusion during biting/chewing (p=.009). Conclusions: • The use of an oral appliance in treatment of obstructive sleep apnea has limited impact on jaw functions and related symptoms.• The risk of developing pain and functional impairment in the masticatory system appears to be limited among users of oral appliances over a 1-y period.• This therapy is safe and can be recommended as a medical treatment modality.